HUBUNGAN SUPERVISI DENGAN PELAKSANAAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP LANTAI 10 RUMAH SAKIT UMUM ROYAL PRIMA MEDAN TAHUN 2017 - Elis Anggeria; Maria Maria (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
Supervision is an important part of the overall management and leadership responsibilities. So as to manage the nursing care, manager's ability to supervise nursing is urgently required. This study aims to find out relationship between supervision and the implementation of nursing care in the inpatient floor 10 at Royal Prima General Hospital Medan in 2017. This study is descriptive correlative. The population are 40 people and sampling techniques used was saturated sampling, then 40 people were drawn to be samples. Data collection was performed by using observation sheets and questionnaires. Based on the research finding, it is found that there is a relationship between the supervision and implementation of nursing care in the inpatient floor 10 of Royal Prima Hospital Medan in which it is obtained that the data of respondents who supervised well consists of 31 people (77.5%), medium was 7 people (17.5%), and less by 2 people (5%). Respondents who did the implementation of nursing care were 38 people (95%) and those who did not perform 2 people (5%). Spearman test results showed that value of significance of (2 - tailed) was 0.401 or probability (p) above 0.05 (0.401 <0.05), then Ho is accepted. It is concluded that there is not any relationship between supervision and implementation of nursing care in the inpatient floor 10 of Royal Prima Hospital Medan. It is suggested that further studies should be conducted about supervision in the implementation of nursing care which refers to the standard operating procedures. Keywords: Relationship, Supervision, Implementation, Nursing Care, Hospitalization